Validity of the Symbol Digit Modalities Test as a cognition performance outcome measure for multiple sclerosis - Benedict, Ralph Hb; DeLuca, John; Phillips, Glenn; LaRocca, Nicholas; Hudson, Lynn D; Rudick, Richard (Multiple sclerosis, 2017)
Cognitive and motor performance measures are commonly employed in multiple sclerosis (MS) research, particularly when the purpose is to determine the efficacy of treatment. The increasing focus of new therapies on slowing progression or reversing neurological disability makes the utilization of sensitive, reproducible, and valid measures essential. Processing speed is a basic elemental cognitive function that likely influences downstream processes such as memory. The Multiple Sclerosis Outcome Assessments Consortium (MSOAC) includes representatives from advocacy organizations, Food and Drug Administration (FDA), European Medicines Agency (EMA), National Institute of Neurological Disorders and Stroke (NINDS), academic institutions, and industry partners along with persons living with MS. Among the MSOAC goals is acceptance and qualification by regulators of performance outcomes that are highly reliable and valid, practical, cost-effective, and meaningful to persons with MS. A critical step for these neuroperformance metrics is elucidation of clinically relevant benchmarks, well-defined degrees of disability, and gradients of change that are deemed clinically meaningful. This topical review provides an overview of research on one particular cognitive measure, the Symbol Digit Modalities Test (SDMT), recognized as being particularly sensitive to slowed processing of information that is commonly seen in MS. The research in MS clearly supports the reliability and validity of this test and recently has supported a responder definition of SDMT change approximating 4 points or 10% in magnitude.